2015
DOI: 10.5539/jas.v7n5p175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Ratios and Rates of Enriched Cattle Manure on Leaf Nitrogen Content, Yield and Quality of Tea (Camellia sinensis)

Abstract: Tea (Camelia sinensis) a major cash crop in Kenya is normally grown on highly weathered and strongly acidic soils. Non-judicial use of the recommended inorganic compound fertilizer 25:5:5:5s acidifies the soil and pollutes water masses. Integrated soil fertility management, the combined use of organic and inorganic fertilizer is recommended for higher tea yield and soil health. An experiment was carried out in the Eastern Highlands of Kenya to determine the effect of different ratios and rates of enriched catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…The findings in Timbilil were corroborated by earlier investigations by Njogu et al (2014) which showed a significant correlation of yield with nutrient levels (NPK) on tea and Chimdessa (2016) on maize. Similar findings on responses of tea yield due to N-application rates were also reported by Kamau et al (2003), Kamau (2011), Owuor et al (2009), Owuor et al 2010, Njogu et al (2014 and Tabu et al (2015) who all confirmed that mature clonal tea requires N-fertilizers to enhance yield. However, our results in Kagochi contradicted these findings.…”
Section: Discussionsupporting
confidence: 85%
“…The findings in Timbilil were corroborated by earlier investigations by Njogu et al (2014) which showed a significant correlation of yield with nutrient levels (NPK) on tea and Chimdessa (2016) on maize. Similar findings on responses of tea yield due to N-application rates were also reported by Kamau et al (2003), Kamau (2011), Owuor et al (2009), Owuor et al 2010, Njogu et al (2014 and Tabu et al (2015) who all confirmed that mature clonal tea requires N-fertilizers to enhance yield. However, our results in Kagochi contradicted these findings.…”
Section: Discussionsupporting
confidence: 85%
“…Enriched sheep manure gave high yield compared to control, sheep manure alone and NPK. This is similar to [28] findings on enriched cattle manure used in tea. However, NPKS still gave high yields but season two showed the lowest yields as compared to other seasons (Table 8).…”
Section: Tea Yieldssupporting
confidence: 90%
“…In tea, the rate of nutrient removal depends on the duration of plucking rounds and their intensity. Continuous plucking of the tea leaves leads to the mining of the macronutrients N, P and K, thus making it necessary to replenish the nutrients to the plant (Tabu et al 2015). The harvestable portion of the tea plant contains a high percentage of nutrients, nitrogen (N) being the most abundant nutrient followed by potassium (K), calcium (Ca), phosphorus (P), sulfur (S), magnesium (Mg) and zinc (Zn) (Sultana et al 2014).…”
Section: Nutritional Requirements For Tea Productionmentioning
confidence: 99%